2020
DOI: 10.1186/s40249-020-00687-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of people diagnosed with tuberculosis through routine and active case finding: a community-based study in Kampala, Uganda

Abstract: Background: Routine tuberculosis (TB) notifications are geographically heterogeneous, but their utility in predicting the location of undiagnosed TB cases is unclear. We aimed to identify small-scale geographic areas with high TB notification rates based on routinely collected data and to evaluate whether these areas have a correspondingly high rate of undiagnosed prevalent TB. Methods: We used routinely collected data to identify geographic areas with high TB notification rates and evaluated the extent to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Various studies have reported on the significance of patient risk groups and residency as key determinants in treatment adherence (11,50,68,69). In our modeling, we equally found the two characteristics to be predictive of whether a patient will adhere to treatment or not.…”
Section: Discussionsupporting
confidence: 60%
“…Various studies have reported on the significance of patient risk groups and residency as key determinants in treatment adherence (11,50,68,69). In our modeling, we equally found the two characteristics to be predictive of whether a patient will adhere to treatment or not.…”
Section: Discussionsupporting
confidence: 60%
“…While some interventions are known to find TB cases, such as household contact investigations which identify individuals exposed at home to TB [1], those interventions will not find the majority of those sick with TB, since less than twenty percent of TB transmission is thought to take place within households [12,13]. Thus, geographic analyses on routinely collected data can be used to identify zones in a community where TB cases or risk factors for transmission are concentrated, in order to help public health workers discern where community-based screening efforts may be deployed [3,4,14]. Additionally, areas identified as cold spots may point to zones where there may be a lack of diagnostic services.…”
Section: Plos Onementioning
confidence: 99%
“…A better understanding of local geographic heterogeneity in routinely identified TB cases and the correlation of that heterogeneity with the location of undiagnosed prevalent cases may, therefore, be useful in directing active case-finding interventions to high-risk areas [ 10 ]. Furthermore, there is a need for accurate and early detection of drug-resistant TB (DR-TB) for minimizing the development of drug resistance, effective patient care, and preventing the spread of DR strains [ 11 ].…”
Section: Introductionmentioning
confidence: 99%